A New Modified Video Solution System for Neuroendoscopic Procedures - Amir Saied Seddighi; Amir Nikouei; Afsoun Seddighi; Morteza Hosseini; Mostafa Hosseini; Alireza Zali; Yasaman Arjmand (Iranian Journal of Neurosurgery, 2022)
Background and Aim: Today, neuroendoscopic surgery is gaining popularity because of its minimal damage to normal structures, fewer complications, and excellent clinical results. Using an endoscope and related instruments, surgeons can perform complex surgeries through small incisions, especially for minimally invasive spinal and brain surgeries. Neuroendoscopic systems are currently costly and not portable. Our new video solution is portable at a lower cost and can display and record images in 4K resolution.